ЭЛЕКТРОН АХБОРОТ ТАЪЛИМ МУҲИТИДА КАСБИЙ ТАЪЛИМ ЖАРАЁНЛАРИНИ ЛОЙИҲАЛАШТИРИШНИНГ ДАСТУРИЙ ВА МЕТОДИК ТАЪМИНОТИ - Маматов, Д.Н.; Балтабаев, Ж.О. (FAN va JAMIYAT, 2018)
The article is devoted to the study of stages and models of pedagogical designing of processes of professional education in the electronic information- educational environment.